2015
DOI: 10.2174/0929867321999141212131457
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic P2X Receptors: Structural and Functional Features Depicted by X-Ray and Molecular Modelling Studies

Abstract: The publication of the first crystal structures of the zebrafish P2X4 receptor in 2009 was a pivotal moment; for the first time, researchers were able to interpret their experimental data in a structural context. Several research groups immediately set about using the data to make molecular models of the better-understood mammalian P2X receptors, in order to design and interpret the results of new, more focused structure-function experiments. In 2012, the publication of the crystal structure of zebrafish P2X4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 106 publications
(170 reference statements)
0
14
0
Order By: Relevance
“…The P2X7R with an extended C-terminal tail of 239 aa and an overall length of 595 aa, is the largest in the P2XR family. Transmembrane domains are responsible for the interactions among subunits and the formation of the ion-permeation pathway (Hattori and Gouaux, 2012; Grimes and Young, 2015). The intracellular C-tail interacts with different intracellular molecules such as heat shock proteins (HSP), cytoskeletal components, kinases and possibly also with membrane proteins.…”
Section: The P2x7rmentioning
confidence: 99%
“…The P2X7R with an extended C-terminal tail of 239 aa and an overall length of 595 aa, is the largest in the P2XR family. Transmembrane domains are responsible for the interactions among subunits and the formation of the ion-permeation pathway (Hattori and Gouaux, 2012; Grimes and Young, 2015). The intracellular C-tail interacts with different intracellular molecules such as heat shock proteins (HSP), cytoskeletal components, kinases and possibly also with membrane proteins.…”
Section: The P2x7rmentioning
confidence: 99%
“…In recent years, our understanding of the relationship between the structure and the function of the ATP-gated P2X receptor family of ion channels has been transformed by a series of crystal structures, from the first structure of a P2X receptor, that of Danio rerio P2X4.1 (zfP2X4) in the apo -state, published in 2009 (Kawate et al, 2009 ), via structures of zfP2X4 bound to ATP (Hattori and Gouaux, 2012 ), a Gulf Coast tick ( Amblyomma maculatum ) P2X structure (Kasuya et al, 2016 ), human P2X3 in the apo -, ATP- and antagonist-bound states (Mansoor et al, 2016 ), zfP2X4 bound to the partial agonist CTP (Kasuya et al, 2017a ), to the most recently determined structures of giant panda ( Ailuropoda melanoleuca ) P2X7 (Karasawa and Kawate, 2016 ) and chicken P2X7 (Kasuya et al, 2017b ). These impressive achievements, along with their enabling of the interpretation of a large body of prior mutagenesis data (reviewed in Chataigneau et al, 2013 ; Jiang et al, 2013 ; Alves et al, 2014 ; Samways et al, 2014 ; Grimes and Young, 2015 ; Habermacher et al, 2016 ; Kawate, 2017 ), have led to significant breakthroughs in our understanding of channel architecture, ligand binding, and the mechanisms of channel opening, desensitization and both orthosteric and allosteric antagonism. In addition, the availability of structural data has allowed for the construction and testing of molecular models of those human receptors which still lack direct high-resolution structural data (Alves et al, 2014 ; Ahmadi et al, 2015 ; Caseley et al, 2015 , 2016 ; Farmer et al, 2015 ; Fryatt et al, 2016 ), paving the way for mutational analysis to elucidate antagonist binding sites (Farmer et al, 2015 ; Allsopp et al, 2017 ), and structure-aided drug design (Ahmadi et al, 2015 ; Caseley et al, 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tri-dimensional structure of the P2X7R subunits resembles the shape of a dolphin, in which the extracellular region represents the body (with head and fins) and the two transmembrane helices (TM1 and TM2) represent the tail (Figure 1c). The three ATP-binding pockets, which are supplied by the ATP sites of each pair of two adjacent monomers (Figure 1d), conform to the active P2X7R, which requires three ATP molecules for gating [22,29], and consequently open the low body domain pore, which is formed by the central TM of each one of the three pairs of TM domains. Interestingly, it has been suggested that the occupancy of two of the three ATP-binding pockets is sufficient to activate other P2XRs [30,31].…”
Section: The Homo-trimeric P2x7 Receptor Proteinmentioning
confidence: 99%